(untitled) (Journal of Science and Technology, 2016)
The toxicological potential of Parquetina nigrescens was investigated using Sprague-Dawley rats. Liver enzymes like Aspartate and Alanine aminotranferases (AST/ALT), Alkaline phoshatase(ALP), γ-glutamyl transferase (GGT), as well as some haematological indices (red and white blood cells), and urea levels were assayed as evidence of toxicity. The extract, administered (400-1600 mg kg-1, p.o.) for six weeks did not cause any significant (p < 0.05) changes in RBC counts in comparison with the mean vehicle-treated control. The total WBC count was not affected after 4 weeks of extract administration (400–1600 mg kg-1 p.o), but in the sixth week the mean total WBC count in rats treated with 1600 mg kg-1 p.o of the extract reduced by 49.0 %.The dose range 400–1600 mg kg-1, p.o did not cause any significant (p < 0.05) changes in both the blood AST and ALT levels. The extract, at all dose levels caused an increase of GGT levls within the first two weeks of treatment, implicating the extract in enzyme induction. Mean serum urea levels in all treatment groups remained statistically unchanged over the six-week period. At the dosage range used, the extract did not cause major changes in the biochemical parameters assessed, indicating the liver and kidney had not undergone any toxic assault. However, the authors suggest the WBC count should be monitored when high doses are administered for long period as the highest dose caused a decrease in WBC count.